Kinematic Analysis of 5-axis CNC Laser Processing Machine Based on GSN Control Card. (1st March 2023) - Sun, Yingjie; Yao, Kun; Yuan, Minghai; Mao, Kefu
Abstract: The five axis CNC laser machining machine is widely used in the processing industry with high efficiency and precision and other advantages. Based on the basic principle of kinematics theory on the multi-body system, this paper describes the homogeneous coordinate transformation law of the five-axis laser machining machine tool based on GSN control card, and analyzes the solution of the motion trajectory and converts it into the incremental data of the position of each axis in the coordinate system of the machine tool, which solves the correctness, universality and automation of the numerical control system. It provides a powerful help for the five axis CNC laser machining machine based on GSN control card.